2012
DOI: 10.1038/aps.2011.194
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cardiotoxicity of doxorubicin involves activation of myocardial and circulating matrix metalloproteinases in rats

Abstract: Aim: To investigate the role of matrix metalloproteinases (MMPs) in the responses of rats to a prolonged doxorubicin (DOX) treatment. Methods: Male Wistar rats were used. DOX was administered by intraperitoneal injections of seven doses (cumulative dose was 15 mg/kg). Control animals were treated with saline. Tissue or plasma samples were collected at four and eight weeks after the application of the last dose. Protein levels were determined by immunoblot assay, and MMP activities were measured by gelatin zymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 31 publications
4
38
0
4
Order By: Relevance
“…These results were confirmed with an apparent increase of caspase immunoreactivity of some muscle fibers in Doxo treated animals. This was confirmed by results of several investigators [5,[24][25][26] .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results were confirmed with an apparent increase of caspase immunoreactivity of some muscle fibers in Doxo treated animals. This was confirmed by results of several investigators [5,[24][25][26] .…”
Section: Discussionsupporting
confidence: 87%
“…production of reactive oxygen species (ROS) may be the cause of effects of DOX or through induction of nitric oxide synthases (NOS), leading to nitric oxide (NO) formation. It has been shown that, DOX treatment in vivo leads to cardiomyocytes apoptosis [4] , and increased levels of cleaved caspase-3 in DOX-treated animal's myocytes [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a previous study in rats with doxorubicin-induced cardiomyopathy did not document the active forms of both MMP 2 and 9, while pro-MMM 2 was also identified (Ivanová et al 2012). Inflammatory mediators activate neutrophils which, in turn, cause the release of MMP 9 from their granules (Sternlicht & Werb 2001).…”
Section: Discussionmentioning
confidence: 71%
“…Embora inicialmente fosse esperada imunomarcação aumentada de MMP2 nos grupos tratados com DOX, já que o estresse oxidativo pode ativar MMP e que TIMP2 pode ativar MMP2 (Bourboulia & Stetler-Stevenson 2010), Ivanová et al (2012), ao estudar ratos com cardiomiopatia induzida por DOX, encontraram aumento na atividade miocárdica da pro--MMP2 apenas oito semanas após a indução, quando havia acumulado a dose de 15mg/kg. Na presente pesquisa, apesar de a dose total acumulada ter sido 8 mg/kg, inferior à dose acumulada no citado estudo, acredita-se que o fator tempo possua grande influência na expressão dessas proteínas, fato também relatado por Ivanová et al (2012).…”
Section: Discussionunclassified
“…Na presente pesquisa, apesar de a dose total acumulada ter sido 8 mg/kg, inferior à dose acumulada no citado estudo, acredita-se que o fator tempo possua grande influência na expressão dessas proteínas, fato também relatado por Ivanová et al (2012). Nesse sentido, experimentos têm sido realizados buscando estabelecer curvas de expressão dessas proteínas, correlacionando-as com o tempo pós-aplicação da DOX.…”
Section: Discussionunclassified